A revelação de Deus ao homem: reflexão teológica a partir da Dei Verbum - Paim, José de Souza (2019)
This paper consists of demonstrating the novelty of the revelation of God to man from the dogmatic Constitution Dei Verbum on the divine revelation of the Second Vatican Council. For this, in a first moment, we are going to focus in general aspects of the Second Vatican Council’s history in which the Dei Verbum has arisen. Our intention is meant to lead you to the realization that the new way of conveying the revelation, as it will be shown in the course of this paper, did not come about by chance and did not happen overnight, but it was a result of openness to the Holy Spirit by both Popes who presided over the Council (John XXIII and Paul VI), the Conciliar Priests and the effort to read and interpret the signs of God for the Church in that historical moment. God, through the Holy Spirit, has been bringing signs of renewal in the Church, they could be seen both in documents from the Church's Magisterium and in the renewal movements. The Second Vatican Council has wisely welcomed everything that had already come and indicated the Church the need to return to Jesus Christ, the living Word of the Father, to listen to him obediently and then seek a new way of conveying the doctrine to the modern human being. Because of this, the Council has revised the way of conveying the revelation and realized the need to overcome a conception in which revelation is seen as the communication of divine truths to present it as the communication of the divine life. The revelation is, above all, based on the initiative of God who, through goodness and wisdom has communicated himself to the human being, inviting them to the life of communion with himself. In Jesus Christ, the divine revelation reaches its consummation and through it man are introduced into the life of grace. From the novelty of the revelation addressed by Vatican II in Dei Verbum, there are some practical consequences or fruits in the Church, both in theology and in the liturgy, in catechesis and in evangelization. One of the most important consequences was the recovery of the centrality of the primacy of the Word of God in the life and mission of the Church. In Dei Verbum we notice the central importance given to the Word as the primordial vehicle of God's communication to man, seen from the title of the document, throughout the preamble up to its pinnacle in the last chapter of the Constitution number VI – Sacred Scripture in life of the Church. Reading it in the light of the Holy Spirit, the human being listens to Jesus Christ, the living Word of the Father, and receives salvation. In this sense, still in this paper, we will consider the reality of the Word of God, in Dei Verbum and in the liturgical and evangelizing dimensions of the Church